The ask and the answer - Ness, Patrick (Walker Books London, 2009)
Fleeing before a relentless army, Todd has carried a desperately wounded Viola right into the hands of their worst enemy, Mayor Prentiss. Immediately separated from Viola and imprisoned, Todd is forced to learn the ways of the Mayor's new order. But what secrets are hiding just outside of town?